2010
DOI: 10.1063/1.3330944
|View full text |Cite
|
Sign up to set email alerts
|

TiO 2 thin-film transistors fabricated by spray pyrolysis

Abstract: We demonstrate electron transporting thin-film transistors based on TiO2 films deposited from solution by spray pyrolysis under ambient atmosphere. The field-effect electron mobility is found to depend strongly on the device architecture and the type of source and drain electrodes employed. For optimized transistors a maximum mobility value of 0.05 cm2/V s is obtained. Furthermore, the TiO2 transistors show air-stable operating characteristics with a shelf life time of several months. This is the only report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Application of spray pyrolysis is not limited to powder production. It covers a wide range of non-conventional applications such as preparation of field effect transistor [138,139], solid coating of refractive materials [13] and carbon nanotubes [124,125].…”
Section: Introductionmentioning
confidence: 99%
“…Application of spray pyrolysis is not limited to powder production. It covers a wide range of non-conventional applications such as preparation of field effect transistor [138,139], solid coating of refractive materials [13] and carbon nanotubes [124,125].…”
Section: Introductionmentioning
confidence: 99%
“…3 several research groups have recently suggested titanium oxide (TiO x ) as a cost-effective n-type semiconductor. 4,5 Deposition methods such as metal-organic chemical vapor deposition (MOCVD), 6 atomic layer deposition (ALD), 7 spray pyrolysis, 8 and magnetron sputtering 9 were employed to grow TiO x active layers, which were implemented into working TFT devices.…”
mentioning
confidence: 99%
“…Wöbkenberg et al reported the electron transporting of TiO 2 thin film transistors fabricated by spray pyrolysis, and found the field effect electron mobility depend strongly on the device architecture and S&D (source and drain) electrodes. 11 In the study on the TiO 2-x -based thin film transistors with amorphous and anatase channel layer, the authors pointed out that relationship between the FET performance and the structure of the channel. 12 Moreover, it was proposed that multiplicity of Ti oxidation state such as Ti 2+ , Ti 3+ and Ti 4+ play an important role on the FET performance of the TiO 2-x -based FETs.…”
Section: Introductionmentioning
confidence: 99%
“…SiO 2 was selected as gate insulator, considering that the most reported TiO 2-x -based FETs using SiO 2 as gate insulator. [11][12][13][14][15] The as prepared TiO 2-x (channel)/SiO 2 (gate insulator) interface was investigated using X-ray Photoelectron Spectroscopy (XPS) spectra. The presence of Si-O-Ti cross-linking bonding at the interface was probed, which is proposed to be the origin of the poor performance of the as-prepared FETs.…”
Section: Introductionmentioning
confidence: 99%